A promising engineering strategy for water electro-oxidation iridate catalysts via coordination distortion. Issue 41 (1st May 2019) - Sun, Wei; Wang, Zhiqiang; Zhou, Zhenhua; Wu, Yiyi; Zaman, Waqas Qamar; Tariq, Muhammad; Cao, Li-mei; Gong, Xue-qing; Yang, Ji
Abstract : Distorted IrO6 is more conducive to improving OER activity. Specifically, regulating the transformation of the IrO6 octahedron from D 4h compression to D 4h elongation is very beneficial for reducing the energy of the rate determining step of the OER process. Abstract : Here, we study the relationship between the coordination structure of IrO6 and OER activity in a wide range of oxides with systematic comparisons. The results reveal that distorted IrO6 is more conducive to OER activity. Specifically, for a given material, regulating the transformation of the IrO6 octahedron from D 4h compression to D 4h elongation causes electrons near the E F level to become more delocalized, which is very beneficial for reducing the energy of the rate determining step. Our findings will guide the design and preparation of more efficient iridium-based OER catalysts.